2002
DOI: 10.1104/pp.010794
|View full text |Cite
|
Sign up to set email alerts
|

Transgenic Expression in Arabidopsis of a Polyprotein Construct Leading to Production of Two Different Antimicrobial Proteins

Abstract: We developed a method for expression in Arabidopsis of a transgene encoding a cleavable chimeric polyprotein. The polyprotein precursor consists of a leader peptide and two different antimicrobial proteins (AMPs), DmAMP1 originating from Dahlia merckii seeds and RsAFP2 originating from Raphanus sativus seeds, which are linked by an intervening sequence ("linker peptide") originating from a natural polyprotein occurring in seed of Impatiens balsamina. The chimeric polyprotein was found to be cleaved in transgen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
53
0
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 74 publications
(58 citation statements)
references
References 33 publications
4
53
0
1
Order By: Relevance
“…4A). To directly determine whether the cax mutants have an altered apoplastic pH, the pH of apoplastic fluids from wild-type, cax1, cax3, and cax1/cax3 leaves was measured (François et al, 2002). This revealed that cax1/ cax3 mutants have a significantly higher apoplastic pH than wild-type plants (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…4A). To directly determine whether the cax mutants have an altered apoplastic pH, the pH of apoplastic fluids from wild-type, cax1, cax3, and cax1/cax3 leaves was measured (François et al, 2002). This revealed that cax1/ cax3 mutants have a significantly higher apoplastic pH than wild-type plants (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…A more advanced and durable approach is to engineer transgenic plants that synthesize chimeras of two or more AMPs with different modes of action to develop a broad-spectrum resistance. For example, overexpression of a chimeric cleavable polyprotein precursor containing the mature domains of the plant defensins Dahlia merckii AMP1 (DmAMP1) and RsAFP2 resulted in the efficient release of both bioactive antifungal peptides (François et al, 2002;Thevissen et al, 2004).…”
mentioning
confidence: 99%
“…Some of the polyprotein expression systems have exploited endogenous plant protease activity to liberate multiple POIs connected by protease substrate sequences (François et al ., 2002a; Urwin et al ., 1998; Walker and Vierstra, 2007; Zhang et al ., 2011). However, processing of the polyproteins in this case can only occur in a particular cellular compartment within hosts where the specific proteases are located.…”
Section: Introductionmentioning
confidence: 99%
“…However, the ‘remnant’ 2A residues appended to the carboxyl terminus of the processed proteins could hinder protein activity and/or cellular targeting (François et al ., 2004; Randall et al ., 2004; Samalova et al ., 2006). Removal of the extraneous 2A residues using host endogenous proteases has been attempted in plant (François et al ., 2002a) and mammalian systems (Fang et al ., 2005), yet the requirement of specific endogenous proteases and inability to completely avoid appending remnant protease substrate linker residues to the cleaved POIs have significantly limited its general usefulness. To resolve these problems, we have exploited in vivo self‐excision of the 2A sequence extension via intein‐mediated N‐terminal autocleavage, by fusing an engineered mini‐intein with the 2A sequence through a linker to create the ‘IntF2A’ self‐excising domain.…”
Section: Introductionmentioning
confidence: 99%